An "ohmic-first" self-terminating gate-recess technique for normally-off Al2O3/GaN MOSFET. (20th February 2018) - Wang, Hongyue; Wang, Jinyan; Li, Mengjun; He, Yandong; Wang, Maojun; Yu, Min; Wu, Wengang; Zhou, Yang; Dai, Gang
Abstract: In this article, an ohmic-first AlGaN/GaN self-terminating gate-recess etching technique was demonstrated where ohmic contact formation is ahead of gate-recess-etching/gate-dielectric-deposition (GRE/GDD) process. The ohmic contact exhibits few degradations after the self-terminating gate-recess process. Besides, when comparing with that using the conventional fabrication process, the fabricated device using the ohmic-first fabrication process shows a better gate dielectric quality in terms of more than 3 orders lower forward gate leakage current, more than twice higher reverse breakdown voltage as well as better stability. Based on this proposed technique, the normally-off Al2 O3 /GaN MOSFET exhibits a threshold voltage ( V th ) of ∼1.8 V, a maximum drain current of ∼328 mA/mm, a forward gate leakage current of ∼10 −6 A/mm and an off-state breakdown voltage of 218 V at room temperature. Meanwhile, high temperature characteristics of the device was also evaluated and small variations (∼7.6%) of the threshold voltage was confirmed up to 300 °C.